Eudicots from severely phosphorus-impoverished environments preferentially allocate phosphorus to their mesophyll - Guilherme Pereira, Caio; Clode, Peta L.; Oliveira, Rafael S.; Lambers, Hans (The New phytologist, 2018)
Plants allocate nutrients to specific leaf cell types, with commelinoid monocots preferentially allocating phosphorus (P) to the mesophyll and calcium (Ca) to the epidermis, whereas the opposite is thought to occur in eudicots. However, Proteaceae from severely P-impoverished habitats present the same P-allocation pattern as monocots. This raises the question of whether preferential P allocation to mesophyll cells is a phylogenetically conserved trait, exclusive to commelinoid monocots and a few Proteaceae, or a trait that has evolved multiple times to allow plants to cope with very low soil P availability. We analysed the P-allocation patterns of 16 species from 10 genera, eight families and six orders within three major clades of eudicots across different P-impoverished environments in Australia and Brazil, using elemental X-ray mapping to quantitatively determine leaf cell-specific nutrient concentrations. Many of the analysed species showed P-allocation patterns that differed substantially from that expected for eudicots. Instead, P-allocation patterns were strongly associated with the P availability in the natural habitat of the species, suggesting a convergent evolution of P-allocation patterns at the cellular level, with P limitation as selective pressure and without a consistent P-allocation pattern within eudicots. Here, we show that most eudicots from severely P-impoverished environments preferentially allocated P to their mesophyll. We surmise that this preferential P allocation to photosynthetically active cells might contribute to the very high photosynthetic P-use efficiency of species adapted to P-impoverished habitats.